SWELL1 is a glucose sensor regulating β-cell excitability and systemic glycaemia - Chen Kang (Nature Portfolio, 2018)
Insulin secretion by β-cells is stimulated by glucose and is dependent on the induction of β-cell membrane depolarization, mainly driven by the closure of KATP channels, which in turn promotes voltage-gated Ca2+ channel opening. Here Kang et al. show that the volume-regulated anion channel, SWELL1, is involved in glucose-stimulated calcium increase and insulin secretion.